The role of international standards for environmental protection in improving environmental performance - SAIHI Youcef (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2020)
This paper aims to highlight the development of international environmental protection standards with the emergence of environmental management systems aimed at managing the impact of the institution and ensuring its commitment to local and international environmental policies and laws. There are several criteria developed by governments and international bodies, as well as other indicators adopted by non-governmental organizations, all of which are considered non-binding but are considered modern mechanisms that contribute to improving environmental performance. So, environment protection has become one of the important factors that should be taken into consideration when making investment decisions.